The Effect of Combination Between Chlorine 0.5% and Alcohol 70% to Bacteria’s Growth - Muzhidah Muzhidah; Tintin Sukartini; Arie Sunarno (Universitas Airlangga, 2009)
Introduction : Desinfection process at laringoscope by using alcohol 70% was not effective for hidrofil’s viruses. The activity mechanism of alcohol 70% is protein denaturation, baktericid for vegetative’s and tuberculoside’s cell. Decontamination with chlorine 0.5% and alcohol 70% have an enzyme inactivity, protein denaturation and inactivity sour of nukleat, so that alcohol desinfectan 70% and chlorine 0.5% much better in pursuing growth of microorganism, but the effectivities of chlorine 0.5% and alcohol 70% for amount of germ’s colony at laringoskop still need furthermore clarification. Objective of this study was aimed to explain the effectiveness of combination of alcohol 70% disinfectant and chlorine 0.5% to decrease germ’s colony in laringoscope.Methods : A quasy eksperimental (control group pre-post test) total sampling design was used in this study. Population were all of laringoscope which used at room operate of emergency departemen 5th floor Dr. Soetomo general hospital of Surabaya. The independent variable was 1) combination of alcohol 70% disinfectant and chlorine 0.5%, 2) alcohol 70% disinfectant only and dependent variable was germ’s colony. Data were analyzed by using Paired t-Test with significance level p<0.05.Results : The result showed that there was an effectiveness combination of chlorine 0.5% and alcohol 70% to decrease germ’s colony (p=0.000) and the effectiveness of alcohol 70% to decrease germ’s colony (p=0.591). Conclusion: It can be concluded that combination of chlorine 0.5% and alcohol 70% more effective to decrease germ’s colony in laringoscope. It is recomended that the existence of periodical inspection of laryngoscope to decrease risk of nosocomial infection.